The duty to accept apologies - Fabre, C (Brill Academic Publishers, 2023)
The literature on reparative justice focuses for the most part on the grounds and limits of wrongdoers’ duties to their victims. An interesting but relatively neglected question is that of what - if anything - victims owe to wrongdoers. In this paper, I argue that victims are under a duty to accept wrongdoers’ apologies. To accept an apology is to form the belief that the wrongdoer’s apologetic utterance or gesture has the requisite verdictive, commissive and expressive dimensions; to communicate as much to him; and to recognise that his apology changes one’s normative status in relation to him, and to comport oneself accordingly. Having so construed the acceptance of apologies, I offer a Kantian argument for the duty to accept. I then examine cases in which, it might be thought, there is no such duty. I end the paper by addressing the more fundamental objection that victims do not owe it to wrongdoers to engage in any form of reparative encounter.